A Discrete Limit Theorem for L-Functions of Elliptic Curves - Garbaliauskienė, Virginija; Garbaliauskas, Antanas (Jaunųjų mokslininkų darbai, 2018)
In the paper, we prove the discrete limit theorem in the sense of the weak convergence of probability measures in the space of analytic on DV = {s ∈ C : 1 < σ < 3/2, |t|  0 be a fixed real number such that exp {2πk/h} is an irrational number for all k∈Z\{0}. Then the probability measure μN(LE(s + imh)∈A), A ∈ B(H(DV)), converges weakly to the measure PLE as N→∞.
Keywords: elliptic curve; L-function; limit theorem; weak convergence